In vitro stability and in vivo pharmacokinetics of the novel ketogenic ester, bis hexanoyl (R)-1, 3-butanediol. (January 2021) - Stubbs, Brianna J.; Blade, Thanh; Mills, Scott; Thomas, Jennifer; Yufei, Xu; Nelson, Frederick R.; Higley, Nancy; Nikiforov, Andrey I.; Rhiner, Marisa O.; Verdin, Eric; Newman, John C.
Abstract: A novel ketone ester, bis hexanoyl (R)-1, 3-butanediol (BH-BD), has been developed as a means to elevate blood ketones, for use as an energy substrate and a signaling metabolite. The metabolism of BH-BD and its effects on blood beta-hydroxybutyrate (BHB) levels was evaluated in various in vitro matrices and through analysis of plasma collected from Sprague Dawley rats and C57/BL6 mice in two oral gavage studies. A well-characterized ketone ester, (R)-3-hydroxybutyl (R)-3-hydroxybutyrate (HB–BHB), was used as an active control throughout. In vitro assay results demonstrated that BH-BD likely remains intact in the stomach and is hydrolyzed in the small intestine into hexanoate and (R)-1, 3-butanediol. If absorbed intact, BH-BD is subject to hydrolysis by non-CYP enzymes in liver and esterases in plasma. If BH-BD reaches the lower intestine it is metabolized by gut flora. Plasma BHB delivery increased in a dose-dependent manner in rats and mice following oral administration of BH-BD. All doses of BH-BD were well tolerated. At doses over 3 g/kg, BHB delivery was similar between BH-BD and HB-BHB. The results of these studies support the hydrolysis of BH-BD into hexanoate and (R)-1, 3-butanediol which are metabolized into BHB, delivering a well-tolerated, sustained and dose-dependent increase in plasma BHB in rodents. Graphical abstract: Image 1 Highlights: A novel ketone ester, bis hexanoyl (R)-1, 3-butanediol (BH-BD), has been developed as a means to elevate blood ketones. The metabolism of BH-BD was evaluated in several in vitro matrices and in vivo . BH-BD was hydrolyzed in the presence of intestinal enzymes, plasma, liver microsomes and in ceacal contents. Oral administration of BH-BD resulted in a dose-dependent increase in blood ketones in rodents.